Legal and Social Implications of Illegal Lottery Schemes: A Study of Rokan Hilir District Court Decision Number 257/Pid.B/2023/PN Rhl - Purba, Didin Alberto; Risdalina, Risdalina; Kusno, Kusno (CV. Social Politic Genius (SIGn), 2025)
This study analyzes Decision Number 257/Pid.B/2023/PN Rhl as a case study to unveil the law enforcement paradox regarding illegal lottery schemes. This case employed a hybrid modus operandi combining conventional methods and electronic means. This research employs a normative-empirical juridical method, drawing on statutory, conceptual, and case study approaches. The objective is to dissect the inconsistency in the application of legal instruments and the sociological impact of the verdict. The findings reveal that the Public Prosecutor and the Panel of Judges tended to be pragmatic by applying Article 303 section (1) point 1 of the Penal Code. They disregarded the fact of electronic means usage, which should have been subject to the principle of lex specialis derogat legi generali under Law Number 11 of 2008. This reduces the potential for the impoverishment of perpetrators through maximum fines. Furthermore, the 8 (eight) month prison sentence without a fine against a Defendant who made gambling his livelihood proved ineffective as a deterrent. Such punishment did not address the perpetrator’s root economic motives. Sociologically, this decision reflects structural inequality in law enforcement, with a sharp downward bias against small retailers and a blunt upward bias against major bookies. This condition implies the normalization of gambling as a community economic alternative. This study recommends integrating a more progressive criminal policy, utilizing digital forensics, and revitalizing customary law to comprehensively eradicate the gambling ecosystem.